Readability of information imprinted in patient information leaflets (PILs) in Saudi Arabia: The case of antihypertensive medications - Aljoharah M Algabbani; Shahad A Alzahrani; Salwa M Almomen; Radwan A Hafiz (Elsevier, 2022)
Background: The Saudi Food and Drug Authority (SFDA) requires marketing authorization holders to submit a PIL in both Arabic and English language. However, the readability of imprinted and disseminated Patient information leaflets (PILs) was not assessed extensively in Saudi Arabia. This study aims to assess the readability of PIL of antihypertensive drugs in both Arabic and English languages. Method: This study was a descriptive quantitative analysis conducted in Saudi Arabia in August 2021. PILs of all oral antihypertensive medications in Saudi Arabia were included in the study. The Arabic and English PILs were extracted from the Saudi Drugs Information System (SDI) and pharmaceutical companies' registration documents. The study used Flesch-Kincaid grade level to assess the readability of English and sentence length to assess the Arabic texts. Descriptive analyses were used to assess the readability scores and the mean differences. Results: It was found that almost 88% of English PILs were above recommended readability level compared to 79% of Arabic PILs. About 89% of English PILs of generic and 86% of brand-name medications were above the readability cutoff point compared with 83% of Arabic PILs of generic and 68% of brand-name medications. The means of grade level for readability of PILs for the widely used antihypertensive medications including angiotensin II receptor blockers (ARBs), antiadrenergic, diuretics, Beta-blockers (BBs), calcium channel blockers (CCBs), and combination antihypertensive medications, and CCBs were higher than the recommended readability level (p < 0.05). The highest mean grade level for readability among English PILs was for combinations of antihypertensive agents (9.35 ± 1.38, p 0.01) and among Arabic PILs was for ARBs (6.15 ± 1.62, p < 0.01). Conclusions: The majority of PILs of antihypertensive medications were above the recommended readability level that can be understood by the majority of the public, especially among generic medications and the most widely used antihypertensive medications. The study findings highlight the need of implementing guidelines to improve the readability of information imprinted in PILs and adopt new regulations requiring readability assessment for manufactures before submitting the PILs to the SFDA.